Study of Interpretation and Diversity of Interpretation Languages in Indonesia: An Analysis of Latin, Jawi, Pegon, and Lontara Scripts - Abdullasani; Muhith Marzuki (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
Indonesian Qur’anic exegesis has developed within a highly plural linguistic landscape, making script choice (Latin, Jawi, Pegon, Lontara) a practical and intellectual issue rather than a mere technicality. This study aims to map the socio-intellectual bases of Indonesian mufassirs and to explain how those bases shape linguistic expression and interpretive orientation. Drawing on the notion of “basis mufassir” and the view of script as epistemic infrastructure for transmitting authority and accessibility, the research employs a qualitative, descriptive library approach. Primary data are selected tafsir texts and paratexts (prefaces, glosses, layout), supported by secondary scholarship on pesantren literacy and regional traditions; analysis uses comparative document and content analysis. Findings show patterned alignments: Latin supports academic-contextual exposition and wider public circulation; Jawi sustains Malay-Islamic scholarly networks; Pegon anchors pesantren pedagogy and localized moral discourse; Lontara embeds Qur’anic meaning within Bugis-Makassar cultural literacy. The plurality of scripts enriches reception while maintaining revelatory unity.